PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA PUZZLE UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPS SISWA KELAS 4 SD NEGERI DUKUH 02 SALATIGA TAHUN PELAJARAN 2017/2018 - Dewi Putri Suryanti; Suroso Suroso; Yustinus Yustinus (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2018)
Abstract This study aims to improve the activity and learning outcomes of students of grade 4 SD Negeri Dukuh 02 Salatiga through a model of cooperative type learning Make a Match assisted Puzzle media. The type of research used is collaborative action research (CAR), where the subjects in this study are 4th graders. There are 23 students in this research. The technique that is used to collect the research is non-test techniques for qualitative data and tests for quantitative data. The data analysis technique is using comparative descriptive analysis. The students' active learning in the pre-cycle for the active criteria were 10 students (43.48%), the active criteria were 12 students (52%), and the less active criteria were 1 student (4.35%). After the first cycle, the students' learning activity for active criteria increased to 17 students (73.91%), the active enough criteria decreased to 5 students (21.74%), and the less active criterion remained 1 student (4.35%). Furthermore, after cycle II, for active criteria increased to 20 students (86.96%), the active enough criteria decreased to 3 students (13.04%), and no students were in the less active criterion. From the pre cycle result, 23 students who have learnt social studies, there are 14 students (60,87%) have not been able to reach the minimum completion criteria and 9 students (36,13%) can reach minimum completion criteria. After the first cycle of student learning social studies learning content increased, from 23 students only 6 students (26.09%) who have not been able to reach minimum completion criteria. The success of the student in learning social studies reached 73.91%. After the second cycle students' learning outcomes on social studies learning content increased, from 23 students only 6 students (13.05%) who have not been able to achieve minimum completion criteria. The completeness of the student learning outcomes on the learning content of social studies reaches 86.95% exceeds the predetermined indicator of success. The result of the research shows that the application of cooperative model type learning Make a Match with Puzzle media can improve the activity and learning result of 4th grade students of SD Negeri Dukuh 02 Salatiga. Keywords: Make a Match; Puzzle; Activeness; Learning outcomes; Social studies. Abstrak Penelitian ini bertujuan untuk meningkatkan keaktifan dan hasil belajar siswa kelas 4 SD Negeri Dukuh 02 Salatiga melalui model pembelajaran kooperatif tipe Make a Match berbantuan media Puzzle. Jenis penelitian yang digunakan adalah penelitian tindakan kelas (PTK) kolaboratif dimana subjek dalam penelitian ini adalah siswa kelas 4 yang berjumlah 23 siswa. Teknik yang digunakan untuk mengumpulkan data penelitian ini adalah teknik non tes untuk data kualitatif dan tes untuk data kuantitatif. Sedangkan teknik analisis data yang digunakan adalah analisis deskriptif komparatif. Keaktifan belajar siswa pada pra siklus untuk kriteria aktif sebanyak 10 siswa (43,48%), kriteria cukup aktif sebanyak 12 siswa (52%), dan kriteria kurang aktif sebanyak 1 siswa (4,35%). Setelah siklus I, keaktifan belajar siswa untuk kriteria aktif meningkat menjadi 17 siswa (73,91%), kriteria cukup aktif menurun menjadi 5 siswa (21,74%), dan kriteria kurang aktif tetap sama yaitu 1 siswa (4,35%). Selanjutnya, setelah siklus II, kriteria aktif meningkat menjadi 20 siswa (86,96%), kriteria cukup aktif menurun menjadi 3 siswa (13,04%), dan untuk kriteria kurang aktif tidak ada. Hasil belajar siswa pada muatan pembelajaran IPS pada pra siklus, yaitu dari 23 siswa sebanyak 14 siswa (60,87%) belum dapat mencapai KKM dan sebanyak 9 siswa (36,13%) dapat mencapai KKM. Setelah siklus 1 hasil belajar siswa pada muatan pembelajaran IPS meningkat, dari 23 siswa hanya 6 siswa (26,09%) yang belum dapat mencapai KKM, ketuntasan hasil belajar siswa pada muatan pembelajaran IPS mencapai 73,91%. Setelah siklus II hasil belajar siswa pada muatan pembelajaran IPS meningkat, dari 23 siswa hanya 6 siswa (13,05%) yang belum dapat mencapai KKM, ketuntasan hasil belajar siswa pada muatan pembelajaran IPS mencapai 86,95% melebihi indikator keberhasilan yang telah ditentukan. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran kooperatif tipe Make a Match berbantuan media Puzzle dapat meningkatkan keaktifan dan hasil belajar siswa kelas 4 SD Negeri Dukuh 02 Salatiga. Kata Kunci: Make a Match; Puzzle; Keaktifan; Hasil Belajar; IPS.